2005
DOI: 10.1017/s1355617705050952
|View full text |Cite
|
Sign up to set email alerts
|

Domain-specific cognitive recovery after first-ever stroke: A follow-up study of 111 cases

Abstract: The objective of this study is to examine the prognosis of acute cognitive disorders post-stroke, and to evaluate which clinical factors predict domain-specific cognitive recovery. We followed the course of cognitive functioning in 111 stroke patients and 77 healthy controls by administering two neuropsychological examinations with a 6 to 10 month interval (mean interval, 7.5 6 1.3 months). The baseline examination was administered within three weeks post-stroke (mean interval, 7.9 6 4.2 days). To examine dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
3
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 49 publications
8
125
3
5
Order By: Relevance
“…Previous studies of cognitive deficits after stroke suggest that improvement in cognitive function is possible over time, especially within six months post-stroke; [50][51][52] however, another study suggested that cognitive deficits remain stable in the sub-acute phase of stroke. 53 In this study, the proportion of participants who scored less than 26 points on the MoCA at discharge dropped slightly by 10% at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of cognitive deficits after stroke suggest that improvement in cognitive function is possible over time, especially within six months post-stroke; [50][51][52] however, another study suggested that cognitive deficits remain stable in the sub-acute phase of stroke. 53 In this study, the proportion of participants who scored less than 26 points on the MoCA at discharge dropped slightly by 10% at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…47 and there is evidence that diabetes is associated with reduced recovery of cognitive function after stroke. 48 Diabetes mellitus has been associated with various adverse health effects, and it was found that patients with diabetes mellitus were more likely than normal patients to have low MMSE 49 reduced cerebral blood flow associated with impaired cerebral auto regulation, increased blood viscosity, and greater prevalence of underlying intracranial large-or small-artery disease. 50 Similarly, the reported association between stroke patients with and without diabetes mellitus of other studies 20,21,26,30,31,39,46 found that diabetes mellitus associated with an increased prevalence of post-stroke dementia.…”
Section: Reviewmentioning
confidence: 99%
“…Since CVA is one of the main causes of this type of impairment, the incidence of cogniti ve disorders in the populati on surviving a CVA varies from 12% to 56% (6)(7) . CVA can be considered the main cause of cogniti ve impairment in elderly individuals, aff ecti ng about 50% of pati ents, both in the acute and chronic phases (7)(8) .…”
Section: Descriptoresmentioning
confidence: 99%